Internalizing the Value of Religious Moderation Through Religious Learning and Activities at MTsS Darul Ma'rifah - Tajussubki, Tajussubki; Saifannur, Saifannur (Institut Agama Islam Al-Aziziyah Samalanga, 2025)
Religious moderation is an important value that must be instilled from an early age in the world of education to form a generation that is religious, tolerant, and noble. MTsS Darul Ma'rifah as one of the dayah-based Islamic educational institutions has a strategic role in internalizing the values of moderation to students. This study aims to analyze the process of internalizing the value of religious moderation through religious learning and activities in MTsS Darul Ma'rifah, as well as identify its contribution to the formation of clean political awareness among the younger generation. The approach used is qualitative with a descriptive design. Data collection techniques were carried out through in-depth interviews, participatory observations, and documentation of teachers, madrasah heads, and students. The results of the study show that moderation values such as honesty, justice, responsibility, and tolerance are consistently integrated in religious learning and activities. Non-formal activities such as recitations, commemoration of Islamic holidays, and moral development also strengthen the character of students who are inclusive and not extreme. The internalization of these values also has an impact on the formation of a clean and ethical political awareness in students, which is shown through a tolerant, anti-corruption, and fair attitude in thinking. This research contributes to expanding the understanding of the role of dayah education in the political moral revolution of the younger generation. The limitation of this study lies in the limited scope of the location, so there is a need for further studies at other similar institutions to strengthen the generalization of the results.